2018
DOI: 10.1016/j.oraloncology.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

STING activation enhances cetuximab-mediated NK cell activation and DC maturation and correlates with HPV+ status in head and neck cancer

Abstract: Objectives The intracellular DNA sensor stimulator of interferon genes (STING) has recently been shown to play a vital role in anti-viral and anti-tumor immune responses stimulating cytokine production. While human papillomavirus (HPV) is a causative agent for a subset of head and neck squamous cell carcinoma (HNSCC) with unique etiology and clinical outcome, how the STING pathway is regulated in a virus-induced tumor microenvironment is not well understood. Since STING inactivation likely reflects immunoescap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…1b). Consistent with previous findings [15], Only transfection of HPV-SCC1 cells resulted in a robust type I IFN induction as early as 6h (Fig. 1c).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…1b). Consistent with previous findings [15], Only transfection of HPV-SCC1 cells resulted in a robust type I IFN induction as early as 6h (Fig. 1c).…”
Section: Resultssupporting
confidence: 93%
“…1c). Consistent with previous observations [15], SCC90 cells responded poorly to 2'3'-cGAMP (Fig. 1c).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Vermorken JB. et al and Lu S. et al study [41,42] showed that Canter immunotherapy could be applied together with chemotherapy for HNSCC patients according to HPV status, and further studies of the new biomarkers-immunological, genetic, or molecular-are needed to be initiated to provide novel targets for improvement of HPV associated HNSCC patient therapy. In addition, markers to identify HPV-positive laryngeal cancer patients with improved prognosis are emerging [43].…”
Section: Discussionmentioning
confidence: 99%